Drug dosage in patients with renal failure optimized by immediate concurrent feedback - Falconnier, Ariane D.; Haefeli, Walter E.; Schoenenberger, Ronald A.; Surber, Christian; Martin-Facklam, Meret (Journal of general internal medicine, 2001)
OBJECTIVE: To examine the impact of immediate concurrent feedback on dose adjustment in patients with renal failure.